Modern and postmodern liturature convergence or divegence narrative techniques in virginia woolf's to the lighthouse and john fowles " the collector - Marouf, Hanane (University of Eloued جامعة الوادي, 2018)
يعتبر كل من فرجينيا وولف وجون فاولز ممثلان للرواية الحديثة وما بعد الحداثة والمعروفان باستخدام تقنيات سرد مبتكرة حيث انه غالبا ما تصنف أسالبيهما بمميزات مماثلة ومع ذلك يمكن لتقنياتهما أن تتقارب أو تتباعد. ان هذا البحث هو عبارة عن دراسة أسلوبية تدرس استعمال تقنية تيار الوعي في رواية "إلى المنارة" والسرد المزدوج المتضارب في رواية "الجامع" وبذلك يمكن لنا تحديد الأغراض الأدبية لكلا الكاتبين. وللقيام بذلك اعتمدنا منهج المقارنة الانتقائي انطلاقا من نهج التحليل النفسي و النهج الأسلوبي والنهج السردي وقد أدى النقاش إلى استخلاص المقاربات في التقنيات السردية في كلا الروايتين وتتمثل في البعد البؤري و التلاعب بالزمن كما والتمثيليات الجمالية أما بالنسبة للفروقات والمباعدات في التقنيات السردية فإنها تتسم بتدفق الأفكار وتيار الوعي للشخصيات مما يعطي القارئ منظورا موضوعيا لمفاهيم الواقع والحقيقة في رواية "إلى المنارة" أما في رواية "الجامع" فالتضارب في سرد الأحداث يجبر القارئ على تكوين نظرته الخاصة للرواية في ظل غياب الحقيقة. وقد يمهد هذا البحث الطريق لدراسة موسعة مستقبلا لجوانب أخرى لتقارب وتباعد الأدب الحديث وما بعد الحداثة. Virginia Woolf and John Fowles are two representative figures of the modernist and postmodernist fiction, known for the use of innovative narrative techniques. Their styles are often categorized by some similar features; however, their techniques may converge and diverge. This research is a stylistic investigation of the use of Stream of Consciousness in Woolf’s To the Lighthouse and Double First-person Narration in Fowles’ The Collector. An eclectic comparative approach that draws on insights from psychoanalysis, stylistics and Narratology is adopted to this study. The discussion concerning the convergence of the narrative techniques in the two novels has resulted in the similar implication of aspects of focalisation, time manipulation, and the aesthetic representations. As for the divergence in the narrative techniques, To the Lighthouse’s narrative techniques depict the flow of thoughts of the characters and present the reader with an objective perspective of the notions of reality. However, The Collector’s opposed subjective accounts of events oblige the reader to formulate his/her own comprehensive vision of the novel due to the loss of truth. This research may pave the way for an extended study of aspects in which Modernism and Postmodernism converge and diverge
Keywords: الأدب الحديث, أدب ما بعد الحداثة, تيار الوعي ,السرد المزوج المتضارب ,الاسلوبية , منهج السرد, مفاهيم الواقع; Modernism, Postmodernism, Stream of Consciousness, Double First-person Narration, Stylistics, Narratology, Notions of Reality.